5q- syndrome. - Boultwood, J; Pellagatti, A; Wainscoat, J (2012)
In recent years we have gained great insight into the molecular pathogenesis of the 5q- syndrome, the most distinct of all the myelodysplastic syndromes. It is now recognized that p53 activation, caused by haploinsufficiency for the ribosomal gene RPS14 (mapping to the commonly deleted region), is the probable cause of the erythroid defect in the 5q- syndrome. A mouse model of the human 5q- syndrome has been generated by large-scale deletion of the Cd74-Nid67 interval (containing Rps14) and the crossing of these '5q- mice' with p53-deficient mice ameliorated the erythroid progenitor defect. Recent evidence suggests that haploinsufficiency of the microRNA genes miR-145 and miR-146a may contribute to the thrombocytosis seen in the 5q- syndrome. Emerging data shows that p53 mutation may play a role in disease progression.